Distribution of some elements in Veronica scutellata L. from Bolu, Turkey: Soil-plant interactions - (:unkn) unknown (My University, 2013)
Veronica scutellata L. occurs in moist and wet habitats, such as ponds, marshes and other wetlands. This study was conducted on this species to examine its mineral element uptake status in terms of interactions between soil and plant. Experimental materials were taken from the Southern coast of Black Sea at coordinates 40°36'N and 31°16'E at an altitude of 1400 m above sea level from Bolu - Turkey; using standard methods and plant (root, stem and leaf parts) and soil mineral element measurements (Al, B, Ca, Cu, Fe, K, Mg, Mn, Na, Ni and Zn) were done. During the study, ICP-OES was employed for the measurement of mineral elements. It was observed that considerable amounts of B, Ca, K, Mg, Mn, Na and Zn are accumulated by the plant.
Keywords: Autecology; Grassleaf speedwell; Plant nutrition; Trace elements